Leading Determinants of Dividend Payouts in India: A Disaggregative Analysis - Nisha Mary Thomas, Parina Shrestha, Smita Kashiramka (International Journal of Control and Automation, 2020)
This study undertakes a comprehensive investigation of the factors that influence dividend payouts for Indian firms by disaggregating the firms into (i) manufacturing and service sectors (ii) banking and financial services sector, and materials and chemicals sector and (iii) high dividend paying firms. The results show negative association between earnings per share and dividend payouts, whichsignals that firms with lower net income pay dividends to allay agency problem. The results also indicate that liquid firms pay lower levels of dividends, thereby supporting Security and Exchange Board of India’s (SEBI) stance that Indian firms have the tendency to hoard cash and not distribute the same to the investors. The findings also reveal that profitable Indian manufacturing and service firms are inclined to maintain lower dividend payouts, as they would like to investutilize earnings for good investment opportunities. The results highlight limited ability of Indian banks and financial sector to pay dividends probably due to the burden of non-performing assets.